Cang-ai volatile oil alleviates nasal inflammation via Th1/Th2 cell imbalance regulation in a rat model of ovalbumin-induced allergic rhinitis - Zhou, Yang; Chen, Bojun; Fu, Yi; Wan, Chunping; Li, Huayan; Wang, Lin; Huang, Xiaoyi; Wu, Zhao; Li, Gang; Xiong, Lei; Qin, Dongdong (Frontiers in Pharmacology, 2024)
We previously revealed that Cang-ai volatile oil (CAVO) regulates T-cell activity, enhancing the immune response in people with chronic respiratory diseases. However, the effects of CAVO on allergic rhinitis (AR) have not been investigated. Herein, we established an ovalbumin (OVA)-induced AR rat model to determine these effects. Sprague–Dawley (SD) rats were exposed to OVA for three weeks. CAVO or loratadine (positive control) was given orally once daily for two weeks to OVA-exposed rats. Behavior modeling nasal allergies was observed. Nasal mucosa, serum, and spleen samples of AR rats were analyzed. CAVO treatment significantly reduced the number of nose rubs and sneezes, and ameliorated several hallmarks of nasal mucosa tissue remodeling: inflammation, eosinophilic infiltration, goblet cell metaplasia, and mast cell hyperplasia. CAVO administration markedly upregulated expressions of interferon-γ, interleukin (IL)-2, and IL-12, and downregulated expressions of serum tumor necrosis factor-α, IL-4, IL-5, IL-6, IL-13, immunoglobulin-E, and histamine. CAVO therapy also increased production of IFN-γ and T-helper type 1 (Th1)-specific T-box transcription factor (T-bet) of the cluster of differentiation-4+ T-cells in splenic lymphocytes, and protein and mRNA expressions of T-bet in nasal mucosa. In contrast, levels of the Th2 cytokine IL-4 and Th2-specific transcription factor GATA binding protein-3 were suppressed by CAVO. These cumulative findings demonstrate that CAVO therapy can alleviate AR by regulating the balance between Th1 and Th2 cells.